Air pollutant dispersion around high-rise buildings under different angles of wind incidence. Issue 167 (August 2017) - Yu, Y.; Kwok, K.C.S.; Liu, X.P.; Zhang, Y.
Abstract: Gaseous pollutant originated from a building can disperse with ambient air flow and re-enter the same building under different environmental conditions. In our previous studies, it was revealed that the near-wall dispersion characteristics in a windward emission are significantly different from that in leeward emission for a high-rise building due to the effect of the building on the wind flow. Since the atmospheric wind changes constantly in both wind speed and wind direction, such that the wind rarely blows perpendicular to the front or the back of a building, it is important to investigate what occurs under different angles of wind incidence. By means of both physical wind tunnel measurement and simulations using Computational Fluid Dynamics (CFD), we firstly studied the dispersion characteristics around a square-sectioned building. It was found that the building influences on wind flow plays a significant role in the dispersion characteristics and an angle of wind incidence of about 90 degrees is a transition angle for the pollutant dispersion pathway around the building. For angles of wind incidence smaller than 90 degrees, air pollutant will migrate predominantly downward while for angles of wind incidence greater than 90 degrees, the pollutant will migrate predominantly upward. Further tests conducted on a more complicated crucifix-form building model with a re-entry along each building wing showed a similar trend of pollutant dispersion at different angles of wind incidence, with the transition angle shifted to approximately 75–80 degrees. The findings of this study show that building shape and the resultant wind-structure interaction plays a significant role in the pollutant dispersion around a building, thus influencing the air quality at different part of a building. Highlights: Influence of wind incidence angle on pollutant dispersion around building is studied. A transition angle, at which the pathway of pollutant changes, is observed. The flow field around the building impacts the pollutant dispersion process.